Complete plastid genome sequence of Oberonioides microtatantha (Schltr.) Szlach. (Orchidaceae), an endemic herb in China. Issue 2 (1st February 2021) - Liu, Caiqin; Kang, Ning; Liu, Xin; Chen, Yu; Tao, Jun; Zhang, Yue; Zhang, Yanyan; Li, Yunlong; Tang, Guangda; Li, Yuling
Abstract: The species Oberonioides microtatantha, belonging to the family Orchidaceae, is a small lithophytic herb endemic in south China with significant conservation values. The complete plastid genome sequence of O. microtatantha reported here is 144, 989 bp in length, with a large single copy (LSC) region of 83, 920 bp, a small single copy (SSC) region of 13, 063 bp, and a pair of inverted repeat (IRa and IRb) regions of 24, 003 bp each. The plastome consists of 95 genes, including 72 protein-coding genes, 4 ribosomal RNA genes, and 19 transfer RNA genes. The overall GC content is 36.81%. Phylogenetic analysis placed Oberonioides closet to the genus Liparis in Orchidaceae.